1973
DOI: 10.1111/j.1432-1033.1973.tb02977.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Properties of Phenylalanyl‐tRNA and Seryl‐tRNA Synthetases for Normal Substrates and Fluorescent Analogs

Abstract: The kinetics of phenylalanyl-tRNA and seryl-tRNA formation were investigated with tRNAs and aminoacyl-tRNA synthetases from yeast.Phenylalanyl-tRNA synthetase yielded linear Lineweaver-Burk plots with tRNAPhe, phenylalanine, and 1 ,Ne-ethenoadenosine triphosphate ( EATP) as variable substrates. According to equilibrium dialysis in the absence or presence of phenylalaninyl adenosine 5'-phosphate, phenylalanyl-tRNA synthetase possesses one binding site for phenylalanine. For ATP as variable substrate, the deviat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

1974
1974
1980
1980

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 46 publications
2
1
0
Order By: Relevance
“…Serine was found to occupy more than one binding site also at low concentrations which agrees with the earlier finding of non-linear Lineweaver-Burk plots (18). On the other hand, it was shown in the present study that only one serine molecule becomes activated even in the presence of pyrophosphatase (Fig.…”
Section: C0supporting
confidence: 93%
“…Serine was found to occupy more than one binding site also at low concentrations which agrees with the earlier finding of non-linear Lineweaver-Burk plots (18). On the other hand, it was shown in the present study that only one serine molecule becomes activated even in the presence of pyrophosphatase (Fig.…”
Section: C0supporting
confidence: 93%
“…Seryl tRNA synthetase seems to share reaction kinetic features with a number of other aminoacyl tRNA synthetases. A second order dependence of the reaction rate on the tRNA concentration as it was previously demonstrated with the serine enzyme (22,23) and is investigated in more detail in the present study, has also been found with the leucine and tryptophan enzymes from E. coli and beef pancreas (23), respectively. Furthermore, one form of glycyl tRNA synthetase from E. coli shows a Hill coefficient of 2 with tRNA as the varied substrate (24).…”
Section: Discussionsupporting
confidence: 75%
“…Even a t pH 13.0 (0.1 N NaOH), where &-adenosine decomposes rapidly, it was possible to perform fluorescence lifetime measurements within minutes of sample preparation, and the lifetime was found to be 20 ns. If the observations a t lower pH values are not considered sufficient to rule out the participation of the protonatcd form, the observations a t high pH could be consistent either with emission by the unprotonated form 1 or with a protonated form having an excited state pKa no less than 14 or 15, since no appreciable decrease of the yield was seen a t pH 13.0.…”
Section: P H Dependence Of Fluorescence Lifetimesmentioning
confidence: 99%